LONGITUDINAL TRAJECTORIES OF IMMUNE CELLS IN OLDER WOMEN: DATA FROM THE WOMEN'S HEALTH AND AGING STUDIES II. (11th November 2018) - Chen, Y; Li, H; Weng, N; Xue, Q; Fried, L; Liu, Y; Ferrucci, L; Leng, S
Abstract: Previous studies suggest significant age-associated phenotypic remodeling of circulating immune cells (T and B clymphocytes and monocytes) in older adults, a key feature of immunosenescence. However, longitudinal evidence supporting such remodeling for older individuals is scarce. This study aimed to investigate longitudinal trajectories of circulating immune cell phenotyes in community-dwelling older women. Included in this study were WHAS II participants (n=107) aged 70–79 years at baseline with peripheral Blood Mononuclear Cells (PBMCs) collected and cryopreserved from each participant at 3–5 different study visits between 1994/1995 – 2007/2008. Immune cell phenotypes were determined through flow cytometry analyses using the following surface markers: CD3, CD4, CD8, CCR7, CD28, CD45RA, CD38 for T cells; CD24, CD38, CD27, CD19, CD20, IgD for B cells; and CD14, CD16 for monocytes. Their longitudinal trajectories were evaluated using linear mixed model. The results showed that most phenotypes had no cross-sectional association with age at baseline. While most T- and B-cell phenotypes showed significant decrease over time, central memory (CCR7+CD45RA-) CD4+ (0.8% per year, p<.001) and CD8+ (0.18%, p<.001), CD28-CD4+ (0.09%, p<.001) and CD28-CD8+ (0.37%, p<.001) T lymphocytes, and CD27- B lymphocytes showed significant trend of longitudinal increase (0.47% per year, p<.001). Similarly, classical (CD14++CD16-) monocytes showed significant decrease (-0.88% per year, p<.001) while nonclassical (CD14+CD16++) monocytes showed significant annual increase (0.22%, p<.001). These findings emphasize the importance and need for longitudinal studies of age-associated remodeling of immune cell phenotypes in both men and women.